Turismo ou desenvolvimento : o que vem primeiro? O caso de Siribinha no Município do Conde no Litoral Norte da Bahia - Müller, Luciana de Oliveira (2006)
The present work analyzes the relationship between development and tourism and the interdependence between them in the locality of Siribinha in the Coast North of the state of the Bahia. One is about a case study that is aims at to understand the reality of tourism phenomenon and its collaboration in the regional development. Though a boarding historical with technique of research bibliographic and field had been raised the main the two elements that permeate the subjects. It is looked, through the analyze of concrete facts, to clarify the factors that compromise the efficiency of the relationship between the tourism and the regional development.